Kompetensi Manajerial di Perguruan Tinggi Era Globaisasi - Pahlawan Pahlawan (Departement of Mathematics Education, 2024)
Universities need to be managed well, so that universities are able to carry out the educational process well so that they can produce quality products, can provide satisfaction to prospective students and the community as well as in the world of employment. To be able to work well, to meet the expectations of the community and the world employment opportunities, then higher education leaders apply Managerial Competencies, 5 managerial competencies of leaders in creating conducive and quality higher education institutions, namely: Conceptual Competency, Interpersonal Communication Competency, Technical Competency, Time Management Competency, and Decision-Making Competence. It should be used as a reference and benchmark in higher education.